Nature monument "Borački krš": A geoheritage site in Serbia - Timotić Mirjana; Belij Srđan (Zaštita prirode)
Borački krš is a nature monument of geological and geomorphological character. The eruptive complex of Borač represents one of the most interesting and once extremely active Tertiary volcanic areas in Serbia, which has in terms of volcanic activities been inactive for the last 5 million years. It was designated as such for the conservation of geological and geomorphological phenomena, as well as biodiversity and landscape diversity. The specificity and importance of this morphologically distinctive area of scientific, cultural and educational importance is reflected in the type and period of its creation. This nature monument was included in the Inventory of Geoheritage Sites of Serbia (2005) as an Erosional Landform (Sites of Geomorphological Heritage).